The Relationship Of Prenatal Yoga To Back Pain In Pregnant Women - Haslin, Sharfina; Simanjuntak, Netti Meilani; Lestari, Puja (Universitas Islam Jember, 2023)
Back pain is pain in the lumbosacral region and back pain is caused by muscle strain on the nerve roots that is usually felt as pain or stiffness in the back. There are several ways to deal with back pain, one of which is using non-pharmacological methods such as acupuncture techniques, back massage, and prenatal yoga. Prenatal yoga is a sport that pregnant women can do to minimize the discomfort that is often felt during pregnancy will be reduced and body movements will feel comfortable. The initial survey obtained at TPMB Theresia Anggriani in 2023, The study involved 50 pregnant women. Researchers watched 28 pregnant women in their second and third trimesters togather information. The aim of the study was to determine the relationship between prenatal yoga and back pain in pregnant women from TPMB Theresia Anggriani. The research method used is a quantitative method with a descriptive research type, namely cross sectional analysis involving the participation of 34 respondents as samples. The chi-square analysis found that the p-value is very small, less than the significant level (α) of 0. This means that the things we tested are strongly connected. This, it can be concluded that prenatal yoga is related to the occurrence of low back pain in pregnant women who experience TPMB.